2017
DOI: 10.1002/nau.23298
|View full text |Cite
|
Sign up to set email alerts
|

Retropubic versus transobturator tension‐free vaginal tape (TVT vs TVT‐O): Five‐year results of the Austrian randomized trial

Abstract: Aims: To compare outcomes of the retropubic versus the transobturator tension-free vaginal tape (TVT vs TVT-O) at 5 years. Methods: A total of 569 women undergoing surgery for primary stress incontinence were randomized to receive a retropubic or a transobturator tensionfree vaginal tape (TVT or TVT-O). Follow-up at 5 years included clinical examination, urodynamic studies and quality of life. The primary outcome measure was continence defined as a negative cough stress test at a volume of 300 mL. Secondary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Attempts we also made by inquiring new residential address from the national registration office, arranging at least three possible follow-up appointments as well as sending postal questionnaires to women who did not attend the clinical appointment. As previously described [ 14 ], 58% of our patients responded to questionnaires at 5 years, but only 50% were available to complete the clinical examination. Therefore, the reasons for missing data within this trial are that the patient were unreachable by telephone, mail or e-mail, patients withdrawal as well as patients not available to reach the hospital for the clinical examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts we also made by inquiring new residential address from the national registration office, arranging at least three possible follow-up appointments as well as sending postal questionnaires to women who did not attend the clinical appointment. As previously described [ 14 ], 58% of our patients responded to questionnaires at 5 years, but only 50% were available to complete the clinical examination. Therefore, the reasons for missing data within this trial are that the patient were unreachable by telephone, mail or e-mail, patients withdrawal as well as patients not available to reach the hospital for the clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is a secondary analysis utilizing an established database from a previously reported prospective randomized controlled noninferiority study by the Austrian Urogynaecology Working Group [ 3 , 14 ]. The aim of this study was to compare objective and subjective outcomes of TVT versus TVT-O as primary treatment for female stress urinary incontinence (SUI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is the validation of the German translation of the PGI‐S and PGI‐I in patients participating in the Austrian TVT versus TVT‐O Trial (http://ClinicalTrials.gov NCT 00441454) . This study was conducted by the Austrian Urogynecology Working Group (AUB) at 25 units in Austria and Germany, with both regional hospitals and academic hospitals participating.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcome parameters were QoL measures and complications. Three months and 5‐years results of the trial have been reported …”
Section: Methodsmentioning
confidence: 99%